How to Design Personal Financial Planning Based on Maqāṣid al-Sharī‘ah: Evidence from a Real Case Study - Moh Shadam Taqiyyuddin Azka; Rahma Salsabila (FEBI UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze and develop a comprehensive Islamic investment planning framework for an individual investor based on the maqāṣid al-syarī‘ah perspective. The research employs a descriptive qualitative approach with a case study design involving a Sharia-compliant investor with a moderate risk profile. Data were collected through preliminary questionnaires, structured interviews, and analysis of financial documents covering assets, liabilities, cash flow, and existing Islamic financial instruments. The analysis was conducted using eight key financial ratios to assess financial soundness and investment feasibility, followed by the classification of investment objectives into short-, medium-, and long-term horizons. The findings indicate that the client’s financial condition is generally healthy, characterized by strong liquidity and solvency, although the proportion of investment assets relative to net worth remains relatively low. Based on these results, a Sharia-compliant investment portfolio was formulated using the efficient frontier approach, emphasizing a balanced allocation between capital preservation and long-term growth through Islamic instruments such as Sharia savings, sukuk, Islamic mutual funds, Sharia-compliant stocks, and gold. This study demonstrates that structured Islamic investment planning not only enhances long-term financial resilience and wealth accumulation but also promotes ethical responsibility, sustainability, and wealth preservation in line with the objectives of maqāṣid al-syarī‘ah.